Effect of hydrogen sulfide on alpha-synuclein aggregation and cell viability - Elena A. Ostrakhovitch; Eun-Suk Song; Johannah E. Stegemann; Michael McLeod; Tritia R. Yamasaki (Scientific Reports)
Abstract Parkinson’s disease (PD) is a progressive neurodegenerative movement disorder characterized by nigrostriatal degeneration and aggregation of α-synuclein (α-Syn) with accumulation of insoluble aggregates in Lewy bodies. Familial mutations in α-Syn are associated with the development of PD. Accumulation of insoluble aggregates results in neuronal toxicity. Identification of compounds that inhibit seeding activity of α-Syn is of great importance. Here we investigate the potential of H2S donor, sodium hydrosulfide (NaHS), to inhibit α-Syn aggregation. We examined the effect of NaHS on fibril growth kinetics and the structural change of α-Syn fibrils formed by self-seeding and cross-seeding of wild-type (wt) and PD familial α-Syn mutations. NaHS slowed both self- and cross-seeded A53T α-Syn fibril formation but not wild-type fibril formation. We observed a decrease in the formed fibril length in vitro. We examined the effect on fibril formation within cells. NaHS significantly reduced the number and filament length of formed oligomers in an α-Syn overexpressing cell model. Furthermore, NaHS rescued viability of A53T α-Syn overexpressing cells seeded with wt- and mutant preformed fibrils. These results support a conformation-specific effect of hydrogen sulfide on alpha-synuclein aggregation and cell viability which deserves further exploration for therapeutic potential.